Derivation of Analytical Inverse Laplace Transform for Fractional Order Integrator - Yüce, Ali; Tan, Nusret (Journal of Applied Nonlinear Dynamics, 2026)
There is considerable interest in the study of fractional order derivative integrator but obtaining analytical impulse and step responses is a difficult problem. Therefore all methods reported on to date use approximations for the fractional derivative/integrator both for analytical based computations and more relevantly in simulation studies. In this paper, an analytical formula is first derived for the inverse Laplace transform of fractional order integrator, 1/sα where α∈R and 0